Developing A Socio-Spatial Index Methodology for Measuring Cross-Border Mobility - Söylemez, Emrah; Varol, Çiğdem (Geographica Pannonica, 2019)
The article proposes a cross-border mobility model for borderlands by developing a multivariate socio-spatial index. Existing methods of evaluating cross-border mobility tend to focus simply on physical and security dimensions of the state borders. However, because of the complex dynamics of relationships among the countries, a multidimensional approach including the economic, social, administrative and spatial relationships have to be considered holistically. The proposed cross-border mobility modeling and index methodology includes spatial and non-spatial multivariate data for assessing the permeability of state borders by using fuzzy logic methods. GIS techniques are used to combine economic, social, administrative and spatial dimensions of relationships for creating the multivariate socio-spatial index and to visualize the results. The results of the proposed methodology experienced for the borderlands of Turkey show that measuring the degree of cross-border mobility can improve the understanding of relationships among the states for developing more effective cross-border policies.
Keywords: fuzzy membership; socio-spatial data; multivariate index; cross-border mobility